Dynamic High‐Pressure Microfluidization Treatment of Rice Bran: Effect on Pb(II) Ions Adsorption In Vitro. Issue 7 (11th July 2018) - Wang, Li; Wu, Jue; Luo, Xiaohu; Li, Yongfu; Wang, Ren; Li, Yanan; Li, Juan; Chen, Zhengxing
Abstract : Abstract: Insoluble dietary fiber from rice bran (RBIDF) was treated with dynamic high‐pressure microfluidization (DHPM). The influence of pressure on the adsorption of Pb(II) capacity of RBIDF was explored in a simulation of the gastrointestinal environment. RBIDF (pH 7.0) displayed the maximal binding capacity (420.74 ± 13.12 μmol/g), at the level of 150 MPa, which was as 1.36 times as the untreated sample. DHPM‐treated RBIDF demonstrated a higher ability to adsorb cholesterol and sodium cholate. Meanwhile, the treatment changed the morphology but did not alter the primary structure. The adsorption capacity is linear to the physicochemical properties of the total negative charges. The adsorption kinetics fit the pseudo‐second‐order model, Pb(II) adsorption mainly occur on the surface of the fiber particulate, this process includes natural physical adsorption and chemical reaction. This study provides a feasible approach for improving the adsorption capacity of RBIDF, especially the adsorption of Pb(II). Practical Application: Dynamic high‐pressure microfluidization can modify biomass adsorption materials effectively as a physically modification. The pretreatment dietary fiber can be used as a low‐cost absorbing heavy metal biosorbent, and can be develop the functional food ingredients in the food industry.